A province wide review of transition practices for young adult patients with type 1 diabetes. Issue 1 (20th April 2020) - Williams, Sarah; Shulman, Rayzel; Allwood Newhook, Leigh Anne; Power, Heather; Guttmann, Astrid; Smith, Sharon; Knight, John; Chafe, Roger
Abstract: Rationale, Aims, and Objectives: Many studies on the transition from paediatric to adult care focus on practices within a single institution or program. We examine the transition for young adults with type 1 diabetes across an entire Canadian province with a small, mostly rural population and high rates of type 1 diabetes: Newfoundland and Labrador (NL). Our aim is to determine how transition is occurring across the jurisdiction and identify methods for improving clinical services for paediatric patients with a chronic condition during their move into adult care. Methods: A provincial diabetes database and hospital admission data were reviewed for a cohort of young adults with type 1 diabetes who transitioned into adult care. Semi‐structured interviews were conducted with paediatric and adult diabetes providers. Results: Between 2008 and 2013, 93 patients with type 1 diabetes transitioned into adult care. Rates of diabetes‐related hospitalizations increased from 15.6/100 person‐years in the 3 years before their 18th birthday to 16.7/100 person‐years in the three‐year period after. Between 2017 and 2019, 15 interviews were conducted across the province's four regional health authorities. Various models of transition care are being employed, reflecting staff and resource availability in different centres. While no formal transition program was identified in either region, some providers, particularly in rural areas, reported being comfortable with their current transition practices. Suggested improvements included more structured processes, shared educational resources, expanding the role played by primary care physicians, and a dedicated transfer clinic. Conclusions: We found different approaches for transitioning patients with diabetes into adult care across NL. Yet this variation may not negatively impact patient outcomes, particularly in rural areas. The approach we employed of combining reviews of administration data with a detailed analysis of current processes could be employed in other jurisdictions to identify appropriate quality improvement initiatives.